CODE-SWITCHING AS DIGITAL IDENTITY PERFORMANCE: GENDERED EXPRESSION ON INDONESIAN TIKTOK - Haya, Fauzia Khusni (Language Horizon: Journal of Language Studies, 2025)
This research examines the practice of code-switching in Indonesian TikTok video content as a linguistic strategy that plays a role in the formation of digital identity and gender representation. Through a descriptive qualitative approach with multimodal discourse analysis, this study analyzes 30 TikTok videos produced by users aged 15-30 who explicitly mix Indonesian and English. The findings indicate that code-switching is used strategically for emotive functions, meaning reinforcement, contemporary communication style, and as markers of social and gender identity. Additionally, code-switching also serves to attract attention, strengthen the memory of bilingual audiences, and reflect the ideological and symbolic dynamics in the digital society. Women tend to use code-switching with a more expressive and affective style, while men more often use code-switching to convey assertive or humorous messages. These findings emphasize that code-switching in social media is not merely a linguistic phenomenon, but a complex performative practice that is laden with social, cultural, and political meanings in an algorithmic and polarized digital space.